Até que a palavra morar faça sentido - Ana Paula Pitzer Angelo (2022)
The research is born from the criticism of the formalist and capitalist logic of production of space and proposes to question the uninventive reproduction of environments that predict hegemonic behaviors. Its starting point is the practical experimentation guided by the structured design process developed during my graduation final project (co-developed in 2019 with Larissa Reis and Marllon Morais and with guidance from Ana Paula Baltazar - EA/UFMG). In the process, interfaces (such as games and body dynamics) are used to formulate demands and stimulate people's reflection about how a space that welcomes their own ways of living and daily activities (current and desired) could be. The aim is, with the descriptions of three of these experiments, with the narratives of those who were involved, and with reflections built essentially from praxis, to highlight the potential of a practice like this, in an effort to rethink the role of the architect and to imagine new ways of working in the field.